The portrait of a stranger: the hypereosinophilic syndrome with cardiac involvement - Ivănescu Andreea-Cristina; Petre Alexandru; Marincaș Andrei Sabin; Bădilă Elisabeta; Dan Gheorghe-Andrei (Sciendo, 2023)
Hypereosinophilic syndrome is a rare clinical condition, and cardiac involvement confers a poor prognosis. Hypereosinophilic myocarditis is a medical emergency and targeted treatment should be started promptly even before a definitive diagnosis could be made.